Performance Comparison of Packet Queuing Algorithm in Wireless Networks - Nor Aida, Mahiddin; Raja Hasyifah, Raja Bongsu; Wan Nor Shuhadah, Wan Nik (2014)
The development in wireless network has changes the fundamental of data communication and networking. However, the increasing data users have caused network congestion. Therefore, a good strategy of packet queuing algorithm is very important to avoid packets drop. This paper aims to propose an effective queuing scheme in wireless network environment. The implementation consider the unfairness problem for the per flow throughput in IEEE 802.11 without the modification of the MAC protocol. We simulate the enhanced packet queuing algorithm using OMNET++. The simulation shows that our algorithm achieves a better result as compared to the existing schemes in enhancing the performance of data communication.